Regional disparities, absorption capacity and Structural Fund payments: A case study of the Czech Republic - Novosák, Jiří; Novosáková, Jana; Hájek, Oldřich; Horváth, Peter (Quaestiones Geographicae, 2017)
The intention of this paper is to provide empirical evidence on how the factors of socio-economic disadvantage and absorption capacity influence the spatial distribution of Structural Fund (SF) payments among the Czech Republic’s micro-regions during the 2007–2013 programming period. The empirical results indicate that agglomeration economies, innovation and entrepreneurship are associated with higher SF absorption capacity and higher SF payments, challenging the tendency for socio-economically disadvantaged regions to converge. SF absorption capacity measured especially by the number of project applications submitted for SF financing and by the average SF budget per project application, is a crucial concept in order to understand the relationship between within-country regional disparities and SF interventions.